Age Is Just a Number: Ontogenetic Conservation in Activation of Blood Clotting Factors VII, X, and XII by Caucasus Blunt-Nosed Viper (Macrovipera lebetina obtusa) Venoms - Katrina Kempson; Abhinandan Chowdhury; Aude Violette; Rudy Fourmy; Raul Soria; Bryan G. Fry (Toxins)
This study examined the pathophysiological effects of venoms from neonate and adult specimens of the viperid snake Macrovipera lebetina obtusa, focusing on their ability to activate various blood clotting factors in human plasma. All venoms exhibited strong procoagulant properties. In concentration–response tests, the clotting potency of the neonate venoms fell within the range of their parents’ maximum clotting velocities and areas under the curve. Intriguingly, females were more potent than males within each age group, but this requires a larger sample size to confirm. Antivenom neutralization efficacy was equipotent across age groups. The venoms potently activated Factor X (FX) robustly, consistent with previous knowledge of this genus. For the first time, the ability to activate Factors VII (FVII) and XII (FXII) was identified in this genus, with FXII exhibiting particularly strong activation. The study found no significant ontogenetic variation in procoagulant venom potency on human plasma, convergent with the Daboia genus, the other large-bodied lineage within the Palearctic viperid clade. However, the activation of FXII and FVII reveals previously undocumented pathways in the procoagulant activity of these venoms, contributing to the broader understanding of venom evolution and its clinical impacts. These findings have implications for venom biodiscovery and the development of antivenoms, highlighting the complexity of clotting factor activation beyond traditional investigations that have myopically focused upon FX and prothrombin pathways, thereby underscoring the importance of exploring additional clotting factors.